STRATEGI KEUNGGULAN BERSAING UMKM SKALA KECIL BIDANG KULINER DALAM UPAYA MENINGKATKAN USAHA DENGAN MENGGUNAKAN ANALISIS SWOT DI PEKANBARU - Novriansyah Rahmat; Jushermi Jushermi; Nursanti Aida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aim to analyze the internal and external environment and formulate alternative strategies for smal-scale SMEs in The culinary field to increase competitiveness in Pekanbaru. The research uses descriptive qualitative method supported by semi-structured interviews to obtain the data used. Respondents include lecturers of economics and lecturers in marketing management as economic experts, The Pekanbaru City Cooperative and Small Medium Enterprise Office, Pekanbaru City Culture and Tourism Office, Riau Province PLUT-KUMKM, Joint Business Groups, and 9 small-scale culinary SMEs. In determining interview informants using judgment sampling technique. In developing a strategy using SWOT Analysis. The results of this study are smallscale culinary MSMEs in Pekanbaru City are in the position of Hold and Maintain by using their strength to take advantage of opportunities, through new product development strategies, and increasing continuous advertising activities.Keyword :MSMEs, Strategy, Advantage Competitive, Matrix IE, Matrix SWOT